Long‐term effect of different tillage systems on the emergence and demography of Bromus diandrus in rainfed cereal fields. (2nd December 2015) - Recasens, J; García, A L; Cantero‐Martínez, C; Torra, J; Royo‐Esnal, A
Summary: The adoption of no‐tillage systems in semi‐arid cereal fields in northern Europe has resulted in difficulties in controlling Bromus diandrus . However, in some fields, lower densities are observed in continuous long‐term no‐tillage management than in other reduced tillage systems. A cumulative effect on the seedbank could promote changes in the period of seedling emergence and in population demography. This study evaluated the effect of long‐term mouldboard plough (MbP), chisel plough (ChP), subsoiler (SS) and no‐tillage (NT) on the population dynamics of B. diandrus . The work was carried out in a barley ( Hordeum vulgare )–wheat ( Triticum aestivum )–barley rotation during three seasons where these soil management systems had been applied for the last 22 years. Cumulative emergence (CE) and densities of B. diandrus followed a gradient of ChP > SS > NT > MbP. This cumulative effect over time resulted in significant differences in population demography. A previous hydrothermal emergence model developed for this species estimated the percentage of emergence prior to the date of sowing to be: 71%, 92% and 53% for the seasons 2008–2009, 2009–2010 and 2010–2011 respectively. Furthermore, the reduction in CE observed was on average 53% in SS, 92% in NT and 98% in MbP in comparison with that recorded in ChP. The long‐term effect of different tillage systems tended to cause changes to soil characteristics (photo‐inhibition of germination, soil temperature, water availability) affecting B. diandrus demography, reaching equilibrium in weed densities over years, which were significantly lower in MbP and NT than in ChP or SS.